HUBUNGAN ANTARA KEMAMPUAN AWAL DAN KEMAMPUAN NUMERIK DENGAN HASIL BELAJAR FISIKA SISWA SMP - Rosida, Halima; Sunarno, Widha; Pur, Supurwoko (Jurnal Materi dan Pembelajaran Fisika, 2012)
The purposes of this research are to find out the correlation between: (1) student physiscs priorknowledge with student physiscs learning achievement, (2) student numerical ability with studentphysiscs learning achievement, (3) student physiscs prior knowledge and student numerical ability withstudent physiscs learning achievement.This research method applied descriptive of correlation. The population was all students of grade VIIIat junior high school Integrated I Purwantoro school year 2010/2011. The sampling technique wasrandom sampling. The amount of sample are 34 students. The tecnique of data collection for studentphysiscs prior knowledge, student numerial ability and student physiscs learning achievement used testtecnique with multiple choise question. The tecnique of data analysis requirement used normality test,independent test and linierity test before multiple regression analysis.According to the result of this research can concluded there is the significant positive correlationbetween: (1) student physiscs prior knowledge with student physiscs achievement ( r 0,486 y.1 = dant 3.1497 t 2.042 0.975;32 = > = ), (2) student numerical ability with student physiscs learningachievement ( r 0.3699 y.1 = dan t 2.252 t 2.042 0.975;32 = > = ), (3) student physiscs prior knowledgeand student numerical ability with student physiscs learning achievement (R 0.58 y.1,2 = danF 7.991 F 3.31 o,o5;2;31 = > = ).Keywords: prior knowledge, numerical ability, student physiscs learning achievement.